Supported Cobalt Oxide Catalysts for the Preferential Oxidation of Carbon Monoxide: An in situ Investigation - Nyathi, Thulani Mvelo (Department of Chemical Engineering, 2021)
The study presented in this thesis has placed great focus on Co3O4-based catalysts for producing CO-free H2-rich gas streams for power generation using proton-exchange or polymer electrolyte membrane fuel cells (PEMFCs). The removal of CO (0.5 – 2%) is essential as it negatively affects the performance of the Pt-based anode catalyst of PEMFCs. Among the various CO removal processes reported, the preferential oxidation of CO (CO-PrOx) to CO2 is a very attractive catalytic process for decreasing the CO content to acceptable levels (i.e.,< 10 ppm) for operating the PEMFC. Co3O4-based catalysts have shown very good catalytic activity for the total oxidation of CO in the absence of H2, H2O and CO2. More specifically, the performance of Co3O4 is known to be influenced by numerous factors such as particle size, particle shape, and the preparation method. As a result, there has also been growing interest in Co3O4 as a cheaper alternative to noble metals for the CO-PrOx reaction. However, the H2 (40 – 75%) in the CO-PrOx feed can also react with O2 (0.5 – 4%) to produce H2O, which consequently decreases the selectivity towards CO2 (based on the total O2 conversion). Aside from H2, the CO-PrOx feed also contains H2O and CO2 which may affect the CO oxidation process as well. The use of Co3O4 as the active catalyst for CO-PrOx can have shortcomings – the main one being its relatively high susceptibility to reduction by H2, forming less active and selective Co-based phases (viz., CoO and metallic Co). Particularly over metallic Co, the conversion pathway of CO can change from oxidation to hydrogenation, forming CH4 instead of CO2. Therefore, the first objective of the work carried out was to investigate the effect of the gas feed components (viz., H2, H2O and CO2; co-fed individually and simultaneously) on the progress of the CO oxidation reaction and the phase stability of Co3O4 over a wide temperature range (50 – 450 °C). It should be noted that the presence of these three gases can also introduce more side reactions, viz., the forward and reverse water-gas shift, respectively, as well as CO and CO2 methanation, respectively. In the supported state, the choice of support, as well as the nature and/or strength of the interaction between the Co3O4 nanoparticles and the support can influence catalytic performance and phase stability. CO oxidation over metal oxides such as Co3O4, is believed to proceed via the Mars-van Krevelen mechanism, which depends on the surface of the catalyst being reducible in order to release lattice oxygen species. Generally, strong metal-support interactions (MSIs) or nanoparticlesupport interactions (NPSIs) can hinder the removal of surface (and bulk) oxygen species, which can negatively affect the catalytic performance. Strong interactions can also promote the solidstate reaction between the species from the nanoparticle with those from the support, leading to the formation of metal-support compounds (MSCs). The supports SiO2, TiO2 and Al2O3 are well known for this phenomenon, and consequently, allow for the formation of silicates, titanates and aluminates, respectively. Support materials such as CeO2, ZrO2 and SiC, are not known for interacting strongly with nanoparticles and often do not react to form MSCs. Therefore, the second objective of this Ph.D. study was to investigate the effect of different support materials (viz., CeO2, ZrO2, SiC, SiO2, TiO2 and Al2O3) on the catalytic performance and phase stability of Co3O4 under different CO-PrOx reaction gas environments. Before carrying out the lab-based experiments, theoretical evaluations were performed by means of thermodynamic calculations based on the Gibbs-Helmholtz Equation. The calculations helped determine the equilibrium conversions of each gas-phase reaction, revealing the extent to which a certain reaction can be expected to take place between 0 and 500 °C. Thermodynamic calculations were also performed to predict the stability of Co3O4, CoO and metallic Co at different temperatures and partial pressure ratios of H2-to-H2O. In the case of supported nanoparticles, the formation of the Co-support compounds - Co2SiO4, CoTiO3 and CoAl2O4 from SiO2, TiO2 and Al2O3, respectively - was shown to be thermodynamically feasible in H2-H2O mixtures. Unsupported Co3O4 nanoparticles were synthesised using the reverse microemulsion technique, while supported Co3O4 nanoparticles were prepared using incipient wetness impregnation. In situ PXRD- and magnetometry-based CO-PrOx catalytic testing was performed in different gas environments as depicted in Figure S.1. The different conditions chosen allowed for the effect of H2, H2O and CO2 on the progress of the CO oxidation reaction and on the reducibility of Co3O4 to be studied. For the first time, this work has identified all the possible gas-phase side reactions (in addition to CO oxidation) that can take place under CO-PrOx conditions. Each reaction could be linked to a specific Co-based phase which is responsible for its occurrence. Furthermore, the temperatures and the extent to which these reactions take place were in-line with the predictions from the thermodynamic calculations. The presence of a support does stabilise the Co3O4 (and CoO) phase over a wide temperature range. Over the weakly-interacting supports (i.e., ZrO2 and SiC), high CO conversions (91.5% and 80.8%, respectively) and O2 selectivities (55.2% and 55.9%, respectively) to CO2 could be obtained, in addition to the improved phase stability of Co3O4. In agreement with the thermodynamic predictions, the presence of Co2SiO4 (7.7%), CoTiO3 (13.8% (from TiO2- anatase) and 8.9% (from TiO2-rutile)), and CoAl2O4 (26.6%) was confirmed using ex situ X-Ray Absorption Spectroscopy in the spent samples of Co3O4/SiO2, Co3O4/TiO2-anatase, Co3O4/TiO2- rutile and Co3O4/Al2O3, respectively, after CO-PrOx. These three samples also exhibited relatively low CO oxidation activities and selectivities, as well as low Co3O4 reducibility.